2008
DOI: 10.1099/mic.0.2008/018283-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PrfA activity in Listeria monocytogenes upon growth in different culture media

Abstract: PrfA is the major transcriptional activator of most virulence genes of Listeria monocytogenes. Its activity is modulated by a variety of culture conditions. Here, we studied the PrfA activity in the L. monocytogenes wild-type strain EGD and an isogenic prfA deletion mutant (EGDDprfA) carrying multiple copies of the wild-type prfA or the mutant prfA* gene (strains EGDDprfApPrfA and EGDDprfApPrfA*) in response to growth in brain heart infusion (BHI), Luria-Bertani broth (LB) or a defined minimal medium (MM) supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 58 publications
(67 reference statements)
2
56
0
1
Order By: Relevance
“…Recent reports Stoll et al, 2008) indicate a close link between the glucose-, mannose-and cellobiose-specific PTS permeases and the modulation of the PrfA activity in L. monocytogenes. Since PrfA is the central transcriptional activator of the major listerial virulence genes, a deeper knowledge of these PTS permeases is therefore of utmost interest for the understanding of the regulation of listerial virulence.…”
Section: Two Members Of the Ptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports Stoll et al, 2008) indicate a close link between the glucose-, mannose-and cellobiose-specific PTS permeases and the modulation of the PrfA activity in L. monocytogenes. Since PrfA is the central transcriptional activator of the major listerial virulence genes, a deeper knowledge of these PTS permeases is therefore of utmost interest for the understanding of the regulation of listerial virulence.…”
Section: Two Members Of the Ptsmentioning
confidence: 99%
“…Even a ptsH insertion mutant, lacking functional HPr and EI, still grows in BHI (Mertins et al, 2007;Stoll et al, 2008). The following studies instead used well-defined media supplemented with glucose, mannose or cellobiose as sole carbon source (Premaratne et al, 1991;Stoll et al, 2008).…”
Section: Pts Permeasementioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, differences in the type of virulence-related proteins synthesized by L. monocytogenes have been reported in BHI-rich medium compared with a minimal medium containing distinct fermentable or nonfermentable carbohydrates (19). For instance, the activity of the master virulence regulator of L. monocytogenes PrfA, which controls expression of functions involved in virulence such as the listeriolysin LLO and the phospholipases PlcA and PlcB (15,20,21), differs in these distinct growth conditions (19). PrfA also modulates the expression of surface proteins, including proteins bearing an LPXTG-sorting motif, GW-rich modules, and the membrane protein ActA, which induces host actin assembly (15,20,21).…”
mentioning
confidence: 99%
“…Investigations into bacterial pathogenesis have revealed an intuitive connection between basic metabolic processes of adaptation and virulence. For example, it has been reported that bacteria alter the transcription of carbohydrate utilization genes and virulence factor-encoding genes in response to the sugar availability encountered in the environment, in particular, in the infected host (44,65,67,69,79). Consequently, regulatory mechanisms that connect carbohydrate metabolism to virulence factor production must have evolved.…”
mentioning
confidence: 99%